Virtual Avatar for Emotion Recognition in Patients with Schizophrenia: A Pilot Study - Marcos-Pablos, Samuel; González-Pablos, Emilio; Martín-Lorenzo, Carlos; Flores, Luis A.; Gómez-García-Bermejo, Jaime; Zalama, Eduardo (Frontiers in Human Neuroscience, 2016)
Persons who suffer from schizophrenia have difficulties in recognizing emotions in others’ facial expressions, which affects their capabilities for social interaction and hinders their social integration. Photographic images have traditionally been used to explore emotion recognition impairments in schizophrenia patients, which lack of the dynamism that is inherent to face to face social interactions. In order to overcome those inconveniences, in the present work the use of an animated, virtual face is approached. The avatar has the appearance of a highly realistic human face and is able to express different emotions dynamically, introducing some advantages over photograph-based approaches such as its dynamic appearance. We present the results of a pilot study in order to assess the validity of the interface as a tool for clinical psychiatrists. 20 subjects who suffer from schizophrenia of long evolution and 20 control subjects were invited to recognize a set of facial emotions showed by a virtual avatar and images. The objective of the study is to explore the possibilities of using a realistic-looking avatar for the assessment of emotion recognition deficits in patients who suffer schizophrenia. Our results suggest that the proposed avatar may be a suitable tool for the diagnosis and treatment of deficits in the facial recognition of emotions.